2016
DOI: 10.1111/nbu.12202
|View full text |Cite
|
Sign up to set email alerts
|

Complementary feeding: Vegetables first, frequently and in variety

Abstract: Diets rich in fruit and vegetables are associated with lower risk of a number of chronic health problems, but the majority of people do not consume enough of these foods. The main predictor of fruit and vegetable intake is enjoyment of these foods, but vegetables are often disliked, especially by children. Food preferences developed in the early years track throughout childhood and beyond and, therefore, it is critical that vegetable liking is promoted at the very earliest opportunity. The start of complementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 47 publications
(111 reference statements)
3
18
0
Order By: Relevance
“…food likes and dislikes developed in the early years predict food likes and dislikes in later years) but noted that this evidence base is mostly observational (as is the case for most life‐course research) and follow‐up periods do not tend to cover later childhood (>7 years). The majority of this evidence comes from prospective cohort studies [as described by Chambers ()] and includes data from large cohorts such as the Avon Longitudinal Study of Parents and Children ( ALSPAC ) (Coulthard et al . , ) and the Infant Feeding Practices Study II (Grimm et al .…”
Section: Food Preferences Developed In the Early Years Track Across Tmentioning
confidence: 99%
See 3 more Smart Citations
“…food likes and dislikes developed in the early years predict food likes and dislikes in later years) but noted that this evidence base is mostly observational (as is the case for most life‐course research) and follow‐up periods do not tend to cover later childhood (>7 years). The majority of this evidence comes from prospective cohort studies [as described by Chambers ()] and includes data from large cohorts such as the Avon Longitudinal Study of Parents and Children ( ALSPAC ) (Coulthard et al . , ) and the Infant Feeding Practices Study II (Grimm et al .…”
Section: Food Preferences Developed In the Early Years Track Across Tmentioning
confidence: 99%
“…Round‐table discussions centred on the following ways of introducing vegetables during complementary feeding as there is both experimental and observational evidence that these can increase children's vegetable acceptance in the short and longer term: repeated exposure to vegetables, offering a wide variety of vegetables and introducing vegetables as first foods. The paper by Chambers () described some of the studies in this evidence base but the round‐table participants agreed that a systematic research review is necessary to ensure that all relevant papers are captured and to assess the quality of the studies using standardised criteria.…”
Section: Ways Of Introducing Vegetables During Complementary Feedingmentioning
confidence: 99%
See 2 more Smart Citations
“…To make the most of this crucial period when babies are receptive to new foods, it has been suggested that offering vegetables exclusively for the first few weeks of complementary feeding with a ‘vegetables first’ approach enhances liking and facilitates acceptance of these foods (Chambers ; Chambers et al . ).…”
mentioning
confidence: 99%